Kendo UI Cookbook : over 50 recipes to help you rapidly build rich and dynamic user interfaces for web and mobile platforms /: over 50 recipes to help you rapidly build rich and dynamic user interfaces for web and mobile platforms. (2014) - Ganatra, Sagar
No abstract available